Interpretive structural modeling in Earned Value Management - Bagherpour, Morteza; Khaje Zadeh, Mohammad; Mahmoudi, Amin; Deng, Xiaopeng (Journal of Civil Engineering and Management, 2020)
The primary purpose of the current study is introducing a comprehensive approach to identify the relationship among different criteria in Earned Value Management (EVM). EVM is a well-known approach in project management context that can monitor schedule and cost performance indexes in projects simultaneously. The EVM detects current project performances and also predicts at completion costs of the project. In this study, employing Interpretive Structural Modelling, interactions which exist among affecting factors on EVM’s success are determined. First, all of the practical factors on EVM are determined and categorized into four main clusters; then the most effective ones are separated from the clusters; eventually, ISM is used based on eleven ultimate critical criteria. The results demonstrate that “Instability in the construction market” and “Macroeconomic indicators” are the most influencing factors affecting the EVM. Finally, a novel method for enhancing the performance of conventional EVM is presented. The proposed approach would be highly applicable for engineering managers who are willing to promote the current performance of the systems. Most studies have been previously carried out on the applications of the EVM in terms of improving final cost and total duration elapsed whereas there is not any particular study on the EVM issue which has stated the key factors that influence the EVM and lasting effect on the project performance. It should be noted that the proposed approach can be employed through the life cycle of any project particularly in construction projects.